Research Paper: The Effect of Wind Stress on Thermocline Development in Persian Gulf in Summer - Seyed Majid Mosaddad (Alzahra University, 2021)
Persian Gulf (PG) is a shallow semi-enclosed sea that connects to the open ocean through the Strait of Hormuz. Thermocline occurs as a sharp decrease in temperature with depth in the subsurface layer as a result of water column classification in Persian Gulf on a seasonal basis. Impulses such as the northwest wind affect this process. In this paper, according to the results of Monte Michel research (1992) and the numerical study of Princeton ocean model (POM), with wind stress in both steady state and monthly average, the formation and development of summer thermocline in PG is investigated. The model results show that with the monthly variable wind, the thermocline develops as indicated by the summer observations. The formation of thermocline seems to decrease the dissolved oxygen in the water column due to lack of mixing as a result of induced stratification. The formation of thermocline seems to reduce the dissolved oxygen in the water column due to the lack of mixing, which is created as a result of water stratification. Also, the formation and development of thermocline as a fast temperature gradient in the water column affects the sound propagation used in offshore detection devices. According to the results of some sources of this research, The thermocline development happens more rapidly in Persian Gulf from spring to summer. Correlation coefficients of temperature and salinity between the model results and measurements were 0.85 and 0.80, respectively. In this paper, the research results obtained from the POM model are compared with the measurements. The rate of thermocline development was found to be between 0.1 to 0.2 meter per day in the Persian Gulf during the 6 months from winter to early summer